Creation of Malaysia's Royal Belum State Park: A Case Study of Conservation in a Developing Country. (March 2015) - Schwabe, Kurt A.; Carson, Richard T.; DeShazo, J. R.; Potts, Matthew D.; Reese, Ashley N.; Vincent, Jeffrey R.
The incentives for resource extraction and development make the conservation of biodiversity challenging within tropical forestlands. The 2007 establishment of the Royal Belum State Park in the Malaysian state of Perak offers lessons for creating protected areas in tropical countries where subnational governments are major forestland owners. This article elucidates the social and political forces that influenced Royal Belum's creation. Those forces included Malaysian conservation groups' efforts to establish the ecological uniqueness of the site and rally public support to protect it; the Perak state government, which is the landowner under Malaysia's constitution, seeking a protection option that would minimize the economic costs to it (and perhaps generate net economic benefits); and the federal government providing a legal framework and support for park protection and ecotourism development. Successful long-run protection of Royal Belum will require action beyond simply designating the area as protected.